Effect of tax audit on the taxpayers’ compliance: a case of Ethiopian Ministry of Revenue, Hawassa and Jimma branches - Nurebo, Beyene Y.; Tarakegn, Genfure; Gutu, Endalew (Asia-Pacific Journal of Science and Technology, 2021)
Objective of the study is to investigate effect of tax audit on the taxpayers’ compliance by employing quantitative research method. Sample size were 156 by using simple random sampling technique and 135 were returned back. Primary data has been collected through questionnaire during 2019 and analyzed using Statistical Package for Social Science Version 20.0. Study revealed that detection of noncompliance, probability of being audited and awareness of taxpayers are positive factors that are affecting compliance of taxpayers significantly. Whereas, changes in government policies, complexity of tax laws and weak and arbitrary penalty are negative factors that affecting compliance of taxpayers significantly. Study conducted by using tax officials who are working in Ministry of revenue in Hawassa and Jimma Branch, but taxpayers were excluded. Future investigators can add taxpayers’ view and widen scope of study. Recommended to the concerned authority to simplify complexity of tax laws that causes inconsistency to interpret and decision, hinders detecting noncompliance, discourage voluntary compliance, and government to add educative penalty scheme to smooth tax administration and to encourage voluntary compliance. Previous studies didn’t consider effect of penalty on compliance of taxpayers and emphasis on the determinants of taxpayers’ compliance on the category “C” taxpayers. Also, previous studies were undertaken based on only category “A” taxpayers, category “C” taxpayers and secondary data from Ethiopian Revenue and Customs Authority (ERCA) rather than Tax Authority. Moreover, the study conducted so far were before the issuance of the current Income Tax Proclamation No 979/2016 and Tax Administration Proclamation No 983/2016.